Barriers and facilitators of peer support work in a large psychiatric hospital: a thematic analysis. Issue 3 (16th June 2021) - Kuek, Jonathan Han Loong; Chua, Hong Choon; Poremski, Daniel
Abstract : Background: Peer support workers are an important addition to the mental healthcare profession. However, much of the literature and knowledge of the peer support role is derived from western countries. This concept is relatively new in Asian countries. Aims: The study sought to improve the understanding of the barriers and facilitators of peer support work in a large psychiatric hospital in Singapore. Methods: This study used qualitative data from a larger mixed-methods study. Thematic analysis was conducted based on the five steps recommended by Braun and Clarke (2006): (1) familiarisation of data whereby transcripts were read and reread, (2) generating initial codes, (3) searching for themes by gathering relevant codes, (4) reviewing themes and (5) defining and naming themes. Results: Four subthemes under the broader notion of facilitators (supportive figures, defined role, opportunities for personal growth and identifying personalised coping strategies) and three subthemes under the concept of barriers (unclear role, hostility from non-peer-support-specialist staff and unsupportive working environments) were identified. Conclusion: Our findings echoed those of previous studies conducted in western countries providing some evidences for the cross-cultural nature of these barriers and facilitators. However, the way their impact can be mitigated or enhanced is likely to be different owing to cultural barriers, such as the general consensus and acceptance of larger personal recovery ideologies. Further research is required in community settings to better understand the boundaries and limitations of our findings. This information will allow us to continue improving peer support worker integration in diverse mental healthcare settings.